COMMUNICATION OF BUSINESS AND GOVERNMENT: IN SEARCH OF AN EFFECTIVE MODEL FOR RUSSIA - Rashid; Evgenievna Prokopenko, Elena (Revista Inclusiones, 2019)
This paper is devoted to an answer to the question: “How are business interests embedded in the mechanism of managerial decision-making in Russia?” To answer the question, the foreign experience of public-private interaction is analyzed, as well as Russianpractices of GR communications between government and business. The purpose of the paper is to construct an effective model of interaction between business and government in Russia, based on positive foreign experience and taking into account the economic, political, and sociocultural characteristics of the country. It is proved that a universal model of interaction between business and government does not exist, but in each national model of communication between business and government, there are effective practices that can be adapted to Russian realities. The novelty of the study is that the forms and technologies of GR communications of business and government are considered as elements of the state administration mechanism. The paper contains some suggestions on the development of mechanisms of interaction between business and government in Russia, capable of changing the paternalistic model of business and government communication to a more effective partnership model.